Okul Öncesi Öğretmenlerinin Sınıf Yönetimi Becerileri ile Problem Çözme Becerileri Arasındaki İlişkinin İncelenmesi - (:unkn) unknown (My University, 2017)
Makalenin özetini buraya yazınız (150-200 kelime) Araştırmanın amacı okul öncesi öğretmenlerinin problem çözme becerileri ile sınıf yönetimi becerileri arasındaki ilişkinin incelenmesidir. Bu ilişkinin yanı sıra araştırmanın alt amaçları doğrultusunda okul öncesi öğretmenlerinin problem çözme becerileri ile sınıf yönetimi becerilerinin çeşitli demografik değişkenlere göre farklılaşması incelenmiştir. İlişkisel tarama modelinde tasarlanan araştırmanın çalışma grubunu 2014-2015 eğitim öğretim yılı bahar yarıyılında İstanbul İli'nde basit tesadüfi örnekleme yöntemiyle seçilen okullarda görev yapan ve araştırmaya katılmayı kabul eden 126 öğretmen oluşturmaktadır. Araştırmada veri toplama aracı olarak okul öncesi öğretmenlerinin problem çözme becerilerini değerlendirmek üzere; Şahin, Şahin ve Heppner tarafından 1993 yılında Türkçe uyarlaması yapılmış olan "Problem Çözme Becerileri Envanteri" ile sınıf yönetimi becerilerini değerlendirmek üzere; Uyanık Balat, Bilgin ve Sezer (2011) tarafından geliştirilen "Okul Öncesi Öğretmenlerine Yönelik Sınıf Yönetimi Ölçeği" kullanılmıştır. Elde edilen veriler uygun analizlerle incelenmiş olup; okul öncesi öğretmenlerinin problem çözme becerileri arttıkça sınıf yönetimi becerilerinin de arttığı sonucuna ulaşılmıştır

The qualities that the teachers bear are important for the development of children with whom they are interacting. Problem solving and classroom management skills are among those qualities. Problem solving skill has an important role in the process of individuals’ accomplishing themselves and coping with their environment (Şahin, 2004). It has such importance that problem solving skills of teachers and prospective teachers have been studied by different researchers based on different variations (Bağçeçi, Kinay, 2013, Bayrak, 2015, Ekinci Vural, 2010, Karaca et al., 2013; Uzunoğlu, Demir, 2014, Yariv, 2013, Yılmaz, 2011). When the results of the study are analyzed, it can be said that individuals who have stronger problem solving skills are more adaptive to the life in their environment. When it is considered that those individuals are teachers, it is put forward that this ability may affect the classroom atmosphere, and it may have relations with teachers’ classroom management skills. Aksoy (2001) suggests that classroom management comprises of the arrangement of physical environment, setting the rules and procedures, interpersonal relations, and discipline. Teachers have an important role in establishing a specific organization in the classroom, in the continuation of activities (Gülay Ogelman & Ersan, 2014), and in the atmosphere created for an easy learning for students (Dinçer & Akgün, 2015). A preschool teacher who is adequate and effective in terms of classroom management will spend most of his/her classroom time on teaching rather than dealing with discipline problems (Denizel Güven & Cevher, 2005). Within the light of given information, the purpose of this research is to study the relations between classroom management and problem solving skills of preschool teachers. Along with the study of this relation within the purpose of this research, the problem solving and classroom management skills of preschool teachers are also examined according to sex, education, occupational experience, and the institutions in which they work. This research is designed according to the relational screening model. Study group of this research consists of 126 teachers who were willing to take part in this research and who work at schools in İstanbul which were chosen with simple random sampling method in Spring semester of 2014-2015 academic year. “Problem Solving Skills Inventory”, which was adapted to Turkish by Şahin, Şahin and Heppner in 1993, was used to examine preschool teachers’ problem solving skills; and, “The Classroom Management Scale for Preschool Teachers”, which was developed by Uyanık Balat, Bilgin and Sezer (2011), was used to examine their classroom management skills. The data derived from the research was analyzed with appropriate method and techniques. It was found out that as preschool teachers’ problem solving skills increase, their classroom management skills increase as well. Along with this, it was also found out that as preschool teachers’ problem solving skills increase, their time management skills and ability to create a more democratic environment increase as well. Furthermore, it was understood that as the teacher’s self-efficacy increases, their problem solving skills increase as well. As preschool teachers’ classroom management skills decreases, their tendency to perform hasty behavior increases when they encounter a problematic situation. It might be concluded that preschool teachers with low problem solving skills do not follow a strategy, and they do not act patiently and calmly when solving a problem. Similarly, as the preschool teachers’ problem solving skill decreases, their tendency to perform avoidant behavior was revealed to happen. It was realized that teachers that have self-confident in terms of problem solving skills and that have a planned attitude are also the ones who have high self-efficacy. Even though there is a variety of domestic and foreign literature that examines teachers’ classroom management and problem solving skills separately based on different variations, there has not been encountered any research that deals with problem solving and classroom management skills together examining their relations. Examination of differentiation in preschool teachers’ problem solving and classroom management skills according to different sexes is taken into consideration as a sub-goal of the study, and it was found out that female teachers’ both problem solving and classroom management skills are much higher compared to male teachers. It was found out in the study that preschool teachers did not show any significant difference in problem solving and classroom solving skills in terms of their associate’s degree, graduate degree, or master’s degree. In another words, preschools teachers’ problem solving and classroom management skills do not vary according to their educational levels. It was found out that preschool school teachers’ problem solving skills in the study group had significant difference in terms of their occupational experience. It was seen that the points of preschool teachers with 0-5 years of occupational experience were lower than the ones with 6-11 years of occupational experience. On the other hand, it was found out that preschool teachers’ classroom management skills did not show significant difference in terms of the variance of occupational experience. When difference between preschool teachers’ problem solving and classroom management skills examined according to the institutions in which they work, preschool teachers’ problem solving and classroom management skills do not show difference according to the institutions such as nursery classes attached to primary schools or kindergartens. Within the lights of findings of this research and related literature, it was suggested that preschool teachers’ problem solving and classroom management skills were affected by teachers’ personal characteristics (sex, educational level, the duration of occupational experience, the type of institution in which they work), and it was shown that teachers’ problem solving skills have an important role in classroom management process (time management, activity planning, physical environment, misbehavior, etc.). In the planning of further research related to the topic, it is necessary to form bigger study groups and deal with different variations. As well as teachers’ education and experience, taking into consideration the importance of teachers’ personal characteristics and skills in the effectiveness and success of educational process.
Study of the Relations between Classroom Management and Problem Solving Abilities of Preschool Teachers
Keywords: Matematik; Eğitim, Eğitim Araştırmaları; Eğitim, Özel